ERNST CASSIRER Y LA METAFÍSICA DE LA VIDA: Una lectura de Sobre la metafísica de las formas simbólicas. - Páez, Jacinto (Revista de Filosofía (00348236), 2025)
This article examines a specific interpretative problem related to Cassirer’s metaphysics of symbolic forms. Divided into four sections, the analysis begins by presenting the interpretative challenges associated with the so-called "fourth volume" of The Philosophy of Symbolic Forms. Next, it explores the various meanings of metaphysics in Cassirer’s texts from the 1920s, a key period for the publication of his principal work. The third section addresses Cassirer’s confrontation with vitalism in general and with Georg Simmel’s metaphysics in particular. Finally, the article connects this reflection with Cassirer’s general concept of philosophy, proposing an integrative view of the role of life in his philosophical system.